A novel sensor based on WO3·0.33H2O nanorods modified electrode for the detection and degradation of herbicide, carbendazim. (1st February 2021) - Ilager, Davalasab; Seo, Hyungtak; Kalanur, Shankara S.; Shetti, Nagaraj P.; Aminabhavi, Tejraj M.
Abstract: In the present-day scenario, it is necessary to establish more flexible, effective and selective analytical methods that are easy to operate and less expensive. Cyclic voltammetry (CV) can be a useful technique to assess minute quantity of pollutants and in this work, an effort has been made to detect the trace quantification from the environmental samples. Herein, electrochemical sensor was fabricated using tungsten oxide nanorod (WO3 ·0.33H2 O) for sensitive detection of fungicide, carbendazim (CBZ). Under optimal conditions, while studying the effect of pH on peak current, the highest peak current was observed at pH 4.2. The degradation of CBZ followed the mixed diffusion-adsorption controlled and quasi-reversible processess at the WO3 ·0.33H2 O/GC electrode surface. Using WO3 ·0.33H2 O/GCE sensor in SWV provided the lowest limit of detection (LOD) and limit of quantification (LOQ) values of 2.21 × 10 −8 M and 7.37 × 10 −8 M, respectively over the concentration ranges of 1.0 × 10 −7 M to 2.5 × 10 −4 M. The proposed method demonstrates potential applicability of the fabricated sensor for soil and water samples analysis in the management of creating a benign environment. Graphical abstract: Image 1 Highlights: Electrochemical sensor for the detection of carbendazim was constructed. The sensor was fabricated using WO3 .0.33H2 O nanorod coated glassy carbon electrode. WO3 .0.33H2 O nanorods enhances the electrochemical response of carbendazim. Carbendazim containing water and soil samples exhibited promising recovery values.